Mapping Social Cohesion in Australia: A Decade of Research on National Attitudes and Values - Alanna Kamp (Cosmopolitan Civil Societies: An Interdisciplinary Journal)
EExisting evidence regarding Australian attitudes and values relating to social cohesion has yet to be comprehensively reviewed. Therefore, there is little understanding of how various programs of research relate to one another, how the information is used, where the data gaps are, and which questions remain unanswered. Drawing upon a scoping review of published research between 2012 and 2022, this paper is a first step towards mapping the extent, range, and nature of the body of national-level research on contemporary Australian social values and cohesion. The review found that there is a dearth of peer-reviewed academic research and what is available focuses on six themes: 1) multiculturalism, cultural diversity, immigration, and racism; 2) Reconciliation; 3) national identity; 4) trust; 5) democracy; and 6) young people. Filling the research gaps will allow better understanding of how macro-level processes may affect intergroup relations and Australians’ attitudes towards issues relating to social cohesion.